2002
DOI: 10.1086/340896
|View full text |Cite
|
Sign up to set email alerts
|

Simulation‐based Investigation of a Model for the Interaction between Stellar Magnetospheres and Circumstellar Accretion Disks

Abstract: We examine, parametrically, the interaction between the magnetosphere of a rotating young stellar object and a circumstellar accretion disk using 2.5-dimensional (cylindrically symmetric) numerical magnetohydrodynamic simulations. The interaction drives a collimated outflow, and we find that the jet formation mechanism is robust. For variations in initial disk density of a factor of 16, variations of stellar dipole strength of a factor of 4, and various initial conditions with respect to the disk truncation ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
81
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 35 publications
(42 reference statements)
5
81
0
Order By: Relevance
“…We note that previous numerical studies of star-disk interactions have shown that differential rotation between the star and the inner disk regions where the stellar magnetosphere is anchored may lead to field lines opening and reconnection, which eventually restores the initial magnetospheric configuration (e.g., Goodson & Winglee 1999;Matt et al 2002;Uzdensky et al 2002;Romanova et al 2004;von Rekowski & Brandenburg 2004;Zanni 2009; see also Alencar 2007, for a review). Magnetospheric reconnection cycles are expected by most numerical models to develop in a few Keplerian periods at the inner disk, and be accompanied by time dependent accretion onto the star and by episodic outflow events as reconnection takes place.…”
Section: In the Context Of Ysosmentioning
confidence: 80%
“…We note that previous numerical studies of star-disk interactions have shown that differential rotation between the star and the inner disk regions where the stellar magnetosphere is anchored may lead to field lines opening and reconnection, which eventually restores the initial magnetospheric configuration (e.g., Goodson & Winglee 1999;Matt et al 2002;Uzdensky et al 2002;Romanova et al 2004;von Rekowski & Brandenburg 2004;Zanni 2009; see also Alencar 2007, for a review). Magnetospheric reconnection cycles are expected by most numerical models to develop in a few Keplerian periods at the inner disk, and be accompanied by time dependent accretion onto the star and by episodic outflow events as reconnection takes place.…”
Section: In the Context Of Ysosmentioning
confidence: 80%
“…We observed that the disk oscillates between "high" and "low" states and expels matter to conical outflows quasi-periodically. The quasi-periodic outbursts associated with the disk-magnetosphere interaction were discussed by Aly & Kuijpers (1990) and observed in simulations by Goodson et al (1997Goodson et al ( , 1999, Matt et al (2002), Romanova et al (2002, hereafter RUKL02), Kato et al (2004), von Rekowski & Brandenburg (2004 and RUKL04. However, none of the earlier simulations concentrated on the propeller stage, and only a few oscillation periods were obtained in earlier simulations.…”
mentioning
confidence: 84%
“…Since it is believed that a sporadic outflow is driven by the star-disk magnetic interaction (Ferreira et al 2000;Matt et al 2002), we examine such cases as well. In this case we adopt a similar function:…”
Section: Time Variabilitymentioning
confidence: 99%